2019
DOI: 10.1089/mdr.2018.0036
|View full text |Cite
|
Sign up to set email alerts
|

PME and Other ESBL-Positive Multiresistant Pseudomonas aeruginosa Isolated from Hospitalized Patients in the Region of Kurdistan, Iraq

Abstract: Nosocomial infections occur worldwide and also in the Kurdistan region. Frequently patients colonized with multiresistant Pseudomonas aeruginosa isolates are encountered in many hospitals. As information is lacking with respect to the mechanisms of resistance responsible for the multiresistant character of the P. aeruginosa isolates and their genetic relationship, isolates were prospectively collected and characterized with respect to their mechanism of resistance. During 2012 and 2013, 81 P. aeruginosa isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The results shown in Table 1 indicate that in Iraq during 2000 through 2020, resistance to 3rd- and 4th-generation standalone cephalosprins; ceftazidime, and cefepime was higher than that of β-lactam/β-lactamase inhibitor combination, amoxicillin-clavulanic acid. Curiously, resistance to piperacillin-tazobactam combination, aminoglycosides (gentamicin and amikacin) was higher than carbapenems such as; imipenem and meropenem [ 70 , 71 , 72 , 73 ]. These increases in antibiotic resistance in these isolates were correlated with the identification of β-lactamases phenotypically.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results shown in Table 1 indicate that in Iraq during 2000 through 2020, resistance to 3rd- and 4th-generation standalone cephalosprins; ceftazidime, and cefepime was higher than that of β-lactam/β-lactamase inhibitor combination, amoxicillin-clavulanic acid. Curiously, resistance to piperacillin-tazobactam combination, aminoglycosides (gentamicin and amikacin) was higher than carbapenems such as; imipenem and meropenem [ 70 , 71 , 72 , 73 ]. These increases in antibiotic resistance in these isolates were correlated with the identification of β-lactamases phenotypically.…”
Section: Resultsmentioning
confidence: 99%
“…Isolates expressing various ESBLs were verified by using a double-disk potentiation method. Studies based on the 402 clinical samples have revealed that the incidence of ESBLs pathogens was comparatively low (13.5%) in 2000, but significantly increased to 61.5% over time [ 70 , 72 , 73 ]. The results shown in Table 2 represent molecular characterization of the ESBL trait with PCR analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results presented in Figure 4 provide evidence for the effects of IMP-resistance on MBLproduction, the study assessed that 19 (82.6%) of the IMP-resistant isolates were MBLproducers while only 4 of the IMP-resistant isolates were non MBL-producers. [17][18][19] In the current study, the frequency of Escherichia coli isolates were (75.5%) while Klebsiella pneumoniae was (24.5%) of the isolates, most of them were isolated from urine samples (66.0%), this result is in conformity with another study conducted by Romero and coworkers [20]. The highest level of antibiotic resistance among Escherichia coli isolates was presented against ampicillin (91.8%) which is shown in (Figure 1).…”
Section: Antibiotic Susceptibility Test (Ast)mentioning
confidence: 99%
“…We performed MLVA according to the method of Brink et al (2014) 12 with minor modifications, and we performed AFLP according to the method of van Burgh et al 13 with minor modifications. We used HpyCHIV4 and MseI restriction enzymes in combination with a selective G residue for HpyCHIV4 and GG for MseI.…”
Section: Molecular Typing and Clonal Relatednessmentioning
confidence: 99%